Role of DNA sequence and nucleosome positioning in higher-order chromatin folding - AlBawardi, Waad (The University of Edinburgh, 2023)
Chromatin is the substrate for all DNA-associated processes and revealing its structure is key to understanding the regulation of nuclear functions. DNA sequence influences the primary positioning and binding affinity of histone octamers, but how this affects higher-order chromatin folding and dynamics is not well understood. Many in vitro chromatin structure studies utilise the Widom 601 DNA template, which strongly positions nucleosomes, and when reconstituted in the presence of linker histones folds into regular fibres approximately 30 nm in diameter. However, as this template uses a synthetic tandem repeat with strong nucleosome positioning properties that are not commonly found in vivo it does not sample the sequence complexity within cells. To explore the properties of more physiological DNA sequences, analogous to what may be observed in cells, I utilised novel DNA templates that contain 25 unique nucleosome positioning sequences derived from the ovine β- lactoglobulin (BLG) gene. Using MNase-seq, BLG sequences were found to position nucleosomes weakly and form irregularly spaced nucleosome arrays. Structural analysis using sucrose gradient sedimentation and small angle X- ray scattering showed that non-repetitive fibres formed disrupted and heterogeneous structures when folded in the presence of the H5 linker histone. Electron microscopy analysis of fibres lacking the H3/H4 tails indicated that non-repetitive arrays have a different folding path compared to 601 fibres. Next, the mechanical properties of the fibres were examined using single- molecule force spectroscopy with magnetic tweezers. This suggested that 601 and non-601 fibres had similar unfolding dynamics in the absence of the H3/H4 tails, and that fibres were fragile under tension. Together, my findings indicate that DNA sequence heterogeneity contributes to chromatin structure variability observed in vivo and can reconcile some of the divergent data observed between in vitro and in vivo studies.
The role of DNA sequence and nucleosome positioning in higher-order chromatin folding
Keywords: Chromatin; Nucleosome positioning; Widom 601; Higher-order chromatin structure; DNA sequence; Chromatin reconstitution